Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1152/ajpcell.1991.261.6.c945
|View full text |Cite
|
Sign up to set email alerts
|

Na(+)-H+ exchanger subtypes: a predictive review

Abstract: In recent years, many reports have appeared describing distinct heterogeneity of proteins that heretofore were considered to be a single species or type. The division of proteins into different classes or subtypes is aided by pharmacological tools such as selective ligands, functional measurements such as those examining kinetic or regulatory differences, and molecular biological approaches that have identified distinct genes coding for similar yet distinguishable gene products. Currently, much effort is direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

1993
1993
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(59 citation statements)
references
References 52 publications
2
55
1
Order By: Relevance
“…We also recall that the amiloride an alogue MIA similarly exhibited only a partial inhib itory effect. There have recently been other reports on Na + IH + antiporters that are less sensitive to amiloride than expected (Clark and Limbird, 1991;Raley-Susman et aI., 1991;Mellergard et aI., 1992). Our observations may thus be explained by the presence of two (or more) different populations of N a + IH + antiporters, with varying sensitivity to amiloride.…”
Section: Acid Extrusion Mechanismsmentioning
confidence: 86%
“…We also recall that the amiloride an alogue MIA similarly exhibited only a partial inhib itory effect. There have recently been other reports on Na + IH + antiporters that are less sensitive to amiloride than expected (Clark and Limbird, 1991;Raley-Susman et aI., 1991;Mellergard et aI., 1992). Our observations may thus be explained by the presence of two (or more) different populations of N a + IH + antiporters, with varying sensitivity to amiloride.…”
Section: Acid Extrusion Mechanismsmentioning
confidence: 86%
“…Because PKC types are frequently implicated in NHE regulation [1,2], we tested their involvement in our model. Figure 2A shows that 1 µM 5-HT further stimulates NHE in the presence of 1 µM PMA.…”
Section: Lack Of Role For Pkcmentioning
confidence: 99%
“…Recent studies have shown that multiple stimuli that rapidly activate ERK pathways also rapidly increase NHE activity in many cell types, particularly in fibroblasts. Those stimuli include, but are not limited to : growth factors that modulate tyrosine phosphorylation cycles, integrins, hyperosmotic stress or cell shrinkage, protein kinase C (PKC), tyrosine phosphorylation cascades and heterotrimeric G proteins [1][2][3][4]. Those similarities provide evidence to suggest that ERK may be a direct proximal component of an NHE regulatory pathway [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NHE-1 is ubiquitously expressed in mammalian cells (for a review see Clark & Limbird, 1991) and has become a focal point of scientific interest. NHE-1 plays an essential role in the development of hypertension (Feig, D'Occhio & Boylan, 1987;Rosskopf, Fromter & Siffert, 1993;Kuroo, 1995) and cardiac ischaemia (Scholz et al, 1995).…”
Section: Introductionmentioning
confidence: 99%